2017
DOI: 10.1038/s41467-017-00406-w
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RIPK1 activation by TAK1-mediated phosphorylation dictates apoptosis and necroptosis

Abstract: Stimulation of TNFR1 by TNFα can promote three distinct alternative mechanisms of cell death: necroptosis, RIPK1-independent and -dependent apoptosis. How cells decide which way to die is unclear. Here, we report that TNFα-induced phosphorylation of RIPK1 in the intermediate domain by TAK1 plays a key role in regulating this critical decision. Using phospho-Ser321 as a marker, we show that the transient phosphorylation of RIPK1 intermediate domain induced by TNFα leads to RIPK1-independent apoptosis when NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
205
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(242 citation statements)
references
References 34 publications
7
205
1
Order By: Relevance
“…Activation of TAK1 kinase activity was previously shown to be a key negative regulator of RDA (Dondelinger et al, 2013; Geng et al, 2017; Mihaly et al, 2014). To address whether there was any crosstalk between TBK1 and TAK1, we induced RDA in WT and Tbk1 −/− MEFs using TNFα and a TAK1 inhibitor: (5Z)-7-Oxozeaenol (5z7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of TAK1 kinase activity was previously shown to be a key negative regulator of RDA (Dondelinger et al, 2013; Geng et al, 2017; Mihaly et al, 2014). To address whether there was any crosstalk between TBK1 and TAK1, we induced RDA in WT and Tbk1 −/− MEFs using TNFα and a TAK1 inhibitor: (5Z)-7-Oxozeaenol (5z7).…”
Section: Resultsmentioning
confidence: 99%
“…The kinase activity of RIPK1 plays a central role in mediating neuroinflammation by promoting the activation of microglia in multiple neurodegenerative diseases including ALS, AD and multiple sclerosis (MS) (Caccamo et al, 2017; Ito et al, 2016; Ofengeim et al, 2015; Ofengeim et al, 2017). RIPK1 is suppressed by inhibitory phosphorylations mediated directly by TAK1 and by the kinases activated by TAK1, including MK2 and IKKs (Dondelinger et al, 2015; Geng et al, 2017; Jaco et al, 2017; Menon et al, 2017). Cells with the loss of TAK1-mediated suppression of RIPK1 kinase can directly promote RIPK1-dependent apoptosis (RDA) upon stimulation by TNFα (Geng et al, 2017; Mihaly et al, 2014; Morioka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this possibility, genetic deletion or pharmacological inhibition of TAK1 and IKKα/β resulted in further sensitization of cell death by activating RIPK1, independently of NF‐κB activation . Subsequent biochemical analyses revealed that RIPK1 phosphorylation on Ser 321 or Ser 25 by TAK1 or IKKα/β in complex‐I prevented the RIPK1‐mediated assembly of the complex‐II/necrosome and then inhibited apoptosis/necroptosis in an NF‐κB‐independent manner . Furthermore, it has been proposed that MAPK‐activated protein kinase 2 (MK2) also induces RIPK1 phosphorylation in complex‐I and protects against complex‐II‐mediated cell death .…”
Section: Introductionmentioning
confidence: 91%
“…After dissociation from TNFR1, complex I will be transformed into complex IIa (comprising TRADD, Fas‐associated protein with death domain [FADD], FLICE‐inhibitory protein [FLIP], and procaspase 8), leading to activation of caspase 8 and rendering RIPK1‐independent apoptosis . Conversely, the formation of complex IIb, consisting of RIPK1, RIPK3, FADD, FLIPs, and caspase 8, can be promoted by knockdown of the nuclear factor kappa B essential modulator (NEMO), blockage of cIAPs, or transforming growth factor β–activated kinase 1 (TAK1) . Hyperactivation of cylindromatosis deubiquitinates RIPK1 and, thus, destabilizes complex I, promoting the formation of complex IIb, which is involved in RIPK1‐dependent apoptosis .…”
Section: Mechanisms Of Necroptosismentioning
confidence: 99%